The Principle of Prudence and Legal Responsibility of Notaries in Beneficial Ownership Verification - Pradhana, Candra Aditya (Journal of Law, Politic and Humanities, 2025)
The purpose of this paper is to describe and analyze issues related to the protection and legal certainty of notaries in verifying the accuracy of corporate BO information, where Permenkum 2/2025 transforms verification from passive to active. The research used a normative approach with a statutory, conceptual, and analytical approach. The analysis reveals an asymmetry between the obligation to verify the accuracy of BO information and the authority possessed by notaries. The absence of investigative authority and cross-verification mechanisms eliminates the substantive nature of notaries' reports on the accuracy of BO information. Protection in the form of liability for notaries who do not or incorrectly include BO information is based on how consistently notaries apply the principle of prudence. If notaries consistently apply this principle, then the element of mens rea in criminal liability and the element of fault in PMH are invalidated, so that notaries cannot be held legally liable.